Mayor Karen Humphrey Celebration at Fresno County Plaza Ballroom - Watkins, Howard::::::::: (1989)
Donald Fischbach, Howard Watkins and Dan Whitehurst All 3 classmates of Hastings College of the Law: Class of 1972